2016
DOI: 10.2527/jas.2015-9993
|View full text |Cite
|
Sign up to set email alerts
|

Changes in feeding behavior patterns and dry matter intake before clinical symptoms associated with bovine respiratory disease in growing bulls

Abstract: Methods to improve accuracy of preclinical detection of bovine respiratory disease (BRD) are needed to reduce the economic impact of this disease, improve animal welfare, and promote more judicious use of antimicrobials in beef cattle. The objectives of this study were to retrospectively characterize time-series deviations in DMI and feeding behavior patterns preceding the display of observed clinical symptoms associated with BRD and to identify those feeding behavior traits that would be most predictive of BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…LFI and RA are two nutritional challenges that can occur under conventional beef and dairy cattle production; however, these challenges differ with respect to predisposing factors and, in some cases, the arising consequences on health and productivity. For example, LFI may occur as a physiological response to parturition (Bertics et al, 1992;Hayirli et al, 2002), infection (Jackson et al, 2016), heat stress (Huber, 1996;Rhoads et al, 2009;Pearce et al, 2012), social and physical stress as occurs for newly received feedlot calves (Loerch and Fluharty, 1999), or due to limited ability to Table 8. Mucosal to serosal inulin (J MS-14C-inulin ) and mannitol (J MS-3H-mannitol ) flux rate, and Gt data for CON (n = 7), RA (n = 7), and LFI (n = 7) steers access feed.…”
Section: Discussionmentioning
confidence: 99%
“…LFI and RA are two nutritional challenges that can occur under conventional beef and dairy cattle production; however, these challenges differ with respect to predisposing factors and, in some cases, the arising consequences on health and productivity. For example, LFI may occur as a physiological response to parturition (Bertics et al, 1992;Hayirli et al, 2002), infection (Jackson et al, 2016), heat stress (Huber, 1996;Rhoads et al, 2009;Pearce et al, 2012), social and physical stress as occurs for newly received feedlot calves (Loerch and Fluharty, 1999), or due to limited ability to Table 8. Mucosal to serosal inulin (J MS-14C-inulin ) and mannitol (J MS-3H-mannitol ) flux rate, and Gt data for CON (n = 7), RA (n = 7), and LFI (n = 7) steers access feed.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for these increased energy demands, mammals display various behavioral responses such as increased sleep, and reductions in social activity, sexual behavior, and feed intake in an effort to conserve energy (Carroll and Forsberg, 2007). Lethargy and reduced feed intake have been well documented in studies monitoring the health of beef cattle (Hutcheson and Cole 1986;Galyean and Hubbert, 1995;Sowell et al, 1999;Quimby et al, 2001;Jackson et al, 2016). These metrics are often the basis for subjective disease detection paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated reductions in feed intake prior to onset of BRD in beef cattle (Jackson et al, 2016;Wolfger et al, 2015b). While automated systems for measuring individual-animal feed intake are becoming more widely available, the prospects for commercial applications of these technologies for early disease detection are limited due to high investment and maintenance costs.…”
Section: Precision Livestock Farmingmentioning
confidence: 99%